Prevalence and clinical patterns of epilepsy in children with spastic cerebral palsy: a cross-sectional study in South India - Josh, G. D. Sushintha; Ramesh, Shanthi; Margaret A., Priya; Ramesh, Jagdeep; Sathees, Parvathy (International Journal of Research in Medical Sciences, 2025)
Background: Cerebral palsy (CP) is frequently accompanied by epilepsy, a comorbidity that exacerbates motor and cognitive impairment. Among the CP subtypes, spastic CP exhibited the highest association with seizures. However, the prevalence and clinical patterns of epilepsy in these children, particularly in the Indian context, remain under-characterized. Objective was to determine the prevalence and characterize the clinical patterns of epilepsy among children with spastic CP in a tertiary care setting in South India. Methods: This cross-sectional study was conducted over 18 months in the pediatric department of a tertiary hospital. A total of 218 children aged 2-14 years with spastic CP were recruited. Epilepsy diagnosis and seizure types were confirmed using ILAE criteria through clinical history and caregiver interviews. Gross motor function was assessed using the gross motor function classification system (GMFCS). Statistical associations were evaluated using chi-square tests and odds ratios (OR) with 95% confidence intervals (CI). Results: Epilepsy was prevalent in 52.2% of the patients. The most common type of seizure was tonic-clonic (31.3%), followed by myoclonic (9.6%) and complex partial seizures (8.7%). Children with quadriplegic (36.5%) and diplegic (35.7%) CP exhibited a higher epilepsy prevalence. Epilepsy was most frequent in GMFCS levels II and III. No significant sex differences were observed. Conclusions: Epilepsy is common in children with spastic CP, particularly among those with quadriplegia, diplegia, and moderate-to-severe motor impairment. Early neurological surveillance and risk-based screening, especially among patients with GMFCS II-IV, may improve detection and long-term outcomes.